Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/dev.22317
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the very low birth weight infant microbiome with neurodevelopment at 2 and 4 years of age

Abstract: Very low birth weight (VLBW) infants (<1500 g) are at risk for poor neurodevelopmental outcomes depending on gestational age (GA), birth weight (BW), and morbidity in early life. The contribution of the gut microbiome is not well understood. Stool samples were collected weekly in the neonatal intensive care unit (NICU) from 24 VLBW infants for 6 weeks after admission and then again at 2 and 4 years of age. The Battelle Development Inventory-2 Screening Test (BDI-2 ST) was administered at 2-and 4-year time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
11
2
Order By: Relevance
“…The relevance of Bifidobacterium in the neurodevelopment of preterm infants was also suggested in the study by Sarkar et al (7). Stool samples from 24 VLBW infants were collected weekly during their NICU stay, and then at 2 and 4 years of age, to assess the GM establishment in the first years of life.…”
Section: Microbiota-gut-brain Axis and Signaling In Preterm Infantsmentioning
confidence: 91%
See 1 more Smart Citation
“…The relevance of Bifidobacterium in the neurodevelopment of preterm infants was also suggested in the study by Sarkar et al (7). Stool samples from 24 VLBW infants were collected weekly during their NICU stay, and then at 2 and 4 years of age, to assess the GM establishment in the first years of life.…”
Section: Microbiota-gut-brain Axis and Signaling In Preterm Infantsmentioning
confidence: 91%
“…Over the last two decades, the impact of the gut microbiota (GM) on host health and physiological processes, including neurodevelopment, has been the subject of increasing research (1)(2)(3)(4). However, only few studies have explored the relationship between GM assembly, brain growth, and neurodevelopment in preterm infants (5)(6)(7)(8)(9)(10)(11). As a result of continuous improvements in neonatal intensive care, the mortality rate of extremely preterm infants [i.e., those with a gestational age (GA) of less than 28 weeks] has dramatically decreased over time.…”
Section: Introductionmentioning
confidence: 99%
“…More evidence is available on preterm infants. In 24 very low birth weight (VLBW) infants, neurodevelopment was examined by the Battelle Development Inventory-2 Screening Test (BDI-2ST) at 2 and 4 years of age [ 37 ]. Correlations between early microbial diversity and specific microbial amplicon sequence variants and BDI-2ST subscales such as cognition, adaptive behavior, and communication were observed, even after adjusting for gestational age, birth weight, and antibiotic exposure.…”
Section: Impact Of Gut Microbiota During Critical Windows Of Developmentmentioning
confidence: 99%
“…Recent evidence suggests that the gut microbiota of preterm infants is associated with early cognitive and behavioral neurodevelopment (Chen et al, 2023 ; Sarkar et al, 2022 ) and has been identified as a potential biomarker of neurodevelopmental delay in preterm infants (Roze et al, 2020 ). Disruption of the maturation and development of the microbiome has also been linked to a number of fatal diseases in preterm infants, including NEC and late‐onset sepsis (Masi & Stewart, 2019 ; Thanert et al, 2021 ).…”
Section: Glial Cells and Mechanismsmentioning
confidence: 99%